Melt flow and heat transfer at the crater end of round billet continuous casting using final electromagnetic stirring - LI Shao-xiang; WANG Pu; LAN Peng; LIU Hua-song; LIU Qi-lin; LI Shu-gui; ZHANG Jia-quan (工程科学学报)
Final electromagnetic stirring (F-EMS) is widely used in the billet and bloom continuous casting process because it effectively improves the as-cast quality. Numerous industrial trials on F-EMS have been conducted; however, the real melt flow and heat transfer characteristics at the crater end remain unclear. In this study, based on a round billet special steel continuous casting process, a coupled three-dimensional numerical model was developed to describe the F-EMS phenomenon. The flow and solidification behavior of the melt in the F-EMS region were obtained by a segmentation calculation model, and the Darcy source term method was employed to suppress the velocity within the mushy region. The effect of stirring current intensity and frequency on the electromagnetic field, melt flow, and heat transfer was investigated numerically. The model was validated using the measured data of magnetic flux density in the stirrer center and the strand surface temperature. According to the simulation results, with every 100 A increase in the current intensity, the maximal magnetic flux density increases by 19.05 mT. The electromagnetic force significantly increases with the increase in current intensity. With the increase in current frequency within 20-40 Hz, the magnetic flux density decreases slightly, whereas the electromagnetic force increases. Moreover, a swirling flow field in the stirrer region is observed under the rotary electromagnetic force, and the tangential velocity of melt increases with the increase in current intensity and frequency. Additionally, the swirling flow enhances the local melt heat transfer at the radial direction of the round strand. As the current intensity and frequency increase, the temperature of the melt in the liquid core decreases, and the center solid fraction at the F-EMS-implemented position increases accordingly.